Contemporary Qualitative Research
VII, 248 p.
Keywords: This volume offers a unique set of research exemplars for science, mathematics and technology educators. The volume explores the important challenge of how to translate leading-edge methodologies into practical research strategies and techniques. The book is divided into three major sections, The Golden Age of Research, Meeting the Research Crises and A New Era of Research, with chapters exploring a variety of methodologies and representational forms and texts. These include historical, narrative, literary, phenomenological, autobiographical, virtual and performance texts, among others. Qualitative Research in Postmodern Times is an exciting and accessible book that will be essential reading for science, mathematics and technology educators interested in new forms of educational research. Beginning researchers will find it practically helpful in planning and conducting their research studies, while experienced researchers will welcome new theoretical insights into postmodern methodologies.